Upaya Gereja Dalam Menghadapi Budaya Aborsi dan Perkawinan Sesama Jenis Yang Bertentangan Dengan Kebenaran Alkitab - Ade Ina Lawajati; Anwar Three Millenium Waruwu; Timotius Tan (PT. Giat Konseling Nusantara, 2025)
This article discusses the efforts of the church in confronting cultures that contradict the truths of the Bible in Indonesia. The Bible, as the divine authority for Christians, plays a central role in spiritual and moral life. With Indonesia being a diverse country rich in culture, customs, and religions, culture is understood as a way of life passed down through generations. Although initially, Nusantara culture was considered at odds with the truth of God's word, the passage of time has brought about cultural phenomena such as same-sex marriage and serious issues related to abortion. The purpose of this research is to analyze the church's efforts in addressing these phenomena, considering legal, religious, and cultural perspectives. Research questions include perceptions of same-sex marriage, challenges faced by the church in addressing abortion issues, the role of church leaders in applying the Word of God, the vital role of the congregation in upholding the truth of the Bible, and church strategies in confronting cultural challenges. The research method employed is qualitative, with text analysis as the primary approach. Research findings indicate conflicts between Indonesian positive law and Bible values regarding same-sex marriage, as well as serious challenges related to abortion among adolescents. The church is tasked with understanding and applying the Word of God accurately, involving the vital role of the congregation and designing effective strategies in facing cultural changes.